Consumer confusion: a systematic review and research directions. Issue 4 (8th June 2021) - Chauhan, Vishakha; Sagar, Mahim
Abstract : Purpose: The purpose of this paper is to systematically review and analyse extant marketing literature on consumer confusion to propose an integrated conceptual framework and highlight important research gaps. Design/methodology/approach: Systematic literature review methodology was followed for article selection. Selected articles were subjected to content analysis to derive thematic as well as descriptive results. Findings: Antecedents, consequences, moderators, mediators and application of the construct in the different contexts have been reported. An integrated framework along with research questions and future directions has also been proposed. Originality/value: To the best of the authors' knowledge, this study is notably the first attempt to systematically review the marketing literature on consumer confusion. The conceptual framework and proposed research questions create a research agenda around the problem of consumer confusion and contribute towards the advancement of extant literature.